Health. Happiness. Inequality. (October 2010) - Karlsson, Martin; Lyttkens, Carl Hampus; Nilsson, Therese
At the beginning of June 2010, the conference 'Health. Happiness. Inequality. Modelling the Pathways between Income Inequality and Health' was held in Darmstadt, Germany. Invited speakers and presenters traveled from all over the world; and researchers from several different subdisciplines were represented at the conference. The common denominator of participants was an interest in how societal income inequality affects individual health and life satisfaction. New and fascinating research results were presented and participants engaged in many interesting discussions.